CASE REPORT OF DOUBLE HETEROZYGOUS PATIENTC WITH SPINAL MUSCULAR ATROPHY - Nonkulovski, Danilo; Duma, Filip; Muaremoska-Kanzoska, Lejla; Kirovski, Ilija; Sofijanova, Aspazija; Zhivkovska, Liljana; Dukovska, Valentina (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Spinal muscular atrophy is an autosomal-recessive disorder characterized by degeneration of motor neurons in the spinal cord and caused by mutations in the survival motor neuron 1 gene, SMN1. In most patients with SMA, the disease is caused by a homozygous deletion or mutation. However, approximately 5% of patients present as compound heterozygotes in which they have only one deletion of SMN1 and a subtle mutation of the other chromosome. The phenotype in these rare cases is much milder than the â€œclassicâ€ forms of SMA, which brings bigger challenge regarding the diagnosis. To describe a case of SMA compound heterozygote and discuss the challenges regarding the diagnosis. Patientâ€™s blood was taken for genetic analysis for SMN1 gene. Automatic DNA extraction, using MLPA method. We present a female patient on the age of 15 months, with clinical features and genetically confirmed spinal muscular atrophy type 2. The genetic analysis showed double heterozygosity for deletion of SMN1, inherited from her mother, as well as genetic conversion of the SMN1 to SMN2 pseudo gene, inherited from the father. The analysis also showed absence of the SMN1 gene and presence of 3 copies of the SMN2 pseudo gene. Fortunately, at our department we are able to treat SMA patients with oral  (Risdiplam) and intrathecal therapy (Nusinersen), which both have shown particular improvement in these patients. Accurate diagnosis of SMA is challenging for compound heterozygotes, but is crucial now, as treatments and gene therapy have become available. Keywords : SMN1 gene, heterozygous, mutation, deletion. https://doi.org/10.55302/JMS2361062n